CONFLICT RESOLUTION IN COMPLEX RENOVATION PROJECTS: INSIGHTS FROM A BRAZILIAN CASE (American Journal of Business Management, Economics and Banking, 2026)
The research article conducts a descriptive single-case study of negotiation patterns during the construction of a major Brazilian corporate office building. The process of renovation work differs from new construction because it encounters continuous interruptions, which generate various conflicting responsibilities and operational constraints that lead to legal disputes among project stakeholders. The project faced major delays because it lacked clear intermediate milestones, which, together with design problems and insufficient subcontractor personnel, led to ongoing disagreements. The negotiation process evolved from using contractual clauses in positional bargaining to an integrative approach that focused on identifying mutual interests between the parties. The research shows that contracts serve as fundamental tools, but they fail to control intricate renovation projects, which need ongoing dialogue and flexible management systems.